A delve into the menstrual problems in teenagers: a cross sectional study in an urban school in Kerala, India - Raveendran, Resmy C.; Jacob, Anju Mariam; Ismail, Jisha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2016)
Background: Onset of menstruation (menarche) is an important milestone in the adolescent girl associated with physical, psychological and social changes. Majority of the girls experience menstrual problems during this period making it even more stressful to handle. Many factors are considered to contribute to these problems of which some may be modifiable. This study was conducted to identify the menstrual problems experienced by young school girls in an urban school in Kerala and to look at any modifiable factors. Methods: Data was collected from girls belonging to the age group of 13 -18 years from an urban private school in Kerala. A detailed semi-structured questionnaire was filled by each student who participated in the study. Information regarding age of menarche, menstrual irregularities, heavy menstrual bleeding, and dysmenorrhoea. BMI of each student was calculated. Results: The mean age of menarche was 12.05 years. The mean weight at menarche was 40.74kg (SD±6.66). 24 girls (21.86%) reported to have irregular menstrual cycles, 76 girls (68.47%) had menstrual cycles coming between 24-35days. 22 girls (19.82%) had cycles between 36-45 days. 11 girls (9.91%) had >45 days duration cycles. 18 girls (16.22%) reported prolonged menstrual flow of >7 days, and 2 girls (1.8%) had scanty flow. 9 girls (8.1%) reported heavy blood loss. 60 girls (54.1%) reported to have moderate flow. 42 girls (37.8%) had mild blood loss. Mild to moderate dysmenorrhoea was reported in 61girls (54.9%), 17 girl (15.3%) reported severe dysmenorrhoea. Conclusions: Menstrual disturbances still pose an important problem in the life of an adolescent. Reproductive awareness programmes should be made more accessible to the adolescents.